Serum ferritin in 15- to 30- year old women at sea level and at high altitude - Paredes Ynga, Andrés A. (2012)
The objective of this study was to determine the effect of hypoxia on iron stores comparing two groups of healthy and sedentary child-bearing women: one group was based in Lima at sea level (100-150 m) and the other included women living in Cerro de Pasco (4,338 m). The study subjects were women aged15 to 30 years old, with no risk factors for iron deficiency. They were randomly selected following these steps: 1. Filling a screening form; 2. Having a medical examination performed, also looking for risk factors that may modify serum ferritin levels; 3.Taking blood samples for measuring Hemoglobin (Hb), Hematocrit, and serum ferritin. Steps 1 and 2 allowed us to exclude women with excessive blood loss or those presenting with conditions that may modify iron metabolism. There were no significant differences with respect to age, but there were some differences in hematological parameters, such as serum ferritin, hemoglobin and hematocrit values. Anemia was more prevalent in those women living at sea level. The results obtained lead us to conclude that the erythropoietic response to high altitude hypoxia does not occur with iron stores depletion in young and healthy women living in high altitude, and changes found may be related to iron bioavailability, which is mediated as a response to high altitude hypoxia.